The Effect of Health Promotion about HIV/AIDS on Adolescents’ Knowledge - Tatisina, Putri Nafa Cindi; Sembiring, Lisma Natalia Br; Nasrianti, Nasrianti; Said, Fathia Inaya; Rainuny, Yance R. (Journal La Medihealtico, 2025)
HIV/AIDS is a disease caused by a virus and can result in AIDS if not treated immediately. One factor that can overcome the transmission of HIV/AIDS is knowledge. Knowledge about HIV/AIDS is very much needed in preventing HIV/AIDS. Objective: To determine the effect of health promotion about HIV/AIDS on the knowledge of adolescents at Kaureh State High School. The study used a pre-experimental design with one group pretest posttest, a random sampling technique, a population of students in grades X and XI with a sample size of 52 respondents using a questionnaire and analyzed using the Wilcoxon test. The results obtained knowledge before health promotion was 56.6% and adolescent knowledge after health promotion was 84.3% there was an increase of 27.8% And the results of the Wilcoxon test with a value of -6.208 with a p-value of 0.000 with a significance of 0.05%. A The results show that there is an effect of health promotion about HIV/AIDS on the knowledge of adolescents at Kaureh State High School. Suggestion: Researchers expect that health promotion will be carried out continuously in collaboration with health services and it is hoped that adolescents will seek information about health from various media.